PEMURNIAN ASAM LINOLEAT TERKONJUGASI HASIL SINTESA DARI RISINOLEAT CASTOR OIL DENGAN KROMATOGRAFI KOLOM SILIKAGEL PERAK NITRAT - Sitorus, Marham; Nainggolan, Bajoka (JURNAL PENELITIAN SAINTIKA, 2014)
Conjugated Linoleic acid (CLA) was sepereted by usingcolomn chromatography with silicagel – AgNO3 as stationaryphase. Seperation based on the differences reversibility ofcoordination bond between double bond and silver ion. Theindreasing number of double bond and trans isomers morestrongly the molecule is retained. Gradien elution was carried outby various n-hexane (H) and Acetone (A) (v/a) e. g: 97.5/2.5; 95/5;90/10; 80/20; 70/30 and 60/40 in 8 vial x 2.5 mL. Each of fractionwas analyzd by using GC,FTIR, UV and GC-MS and It’s comparewith authentic CLA standard and the best was ratio (v/v) of eluen(H/A) 95/5. The composition of product ratio of CLA/linoleic was0,85 : 1 or 77.6 % compared to the authentic standar 1.45/1.